2012
DOI: 10.1111/rda.12003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Lipids Present in Cat and Dog Oocyte by Matrix‐Assisted Desorption Ionization Mass Spectrometry (MALDIMS)

Abstract: ContentsThe aim of the present study was to investigate the level of information on the chemical structures and relative abundances of lipids present in cat and dog oocytes by matrixassisted laser desorption mass spectrometry (MALDI-MS). The MALDI-MS approach requires a simple analysis workflow (no lipid extraction) and few samples (two or three oocytes per analysis in this work) providing concomitant profiles of both intact phospholipids such as sphingomyelins (SM) and phosphatidylcholines (PC) as well as tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
2
27
2
Order By: Relevance
“…Change of lipid phase state in cells during freezing is among the most important factors limiting the cryopreservation of embryos and oocytes. A number of mammalian species are challenging for embryos/oocytes cryopreservation due to the excessive lipid droplet (LD) content (10-12). The problem of high lipid content in oocytes and embryos seems to concern virtually all the representatives of the Carnivora order (5,12), among which a large proportion are endangered species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change of lipid phase state in cells during freezing is among the most important factors limiting the cryopreservation of embryos and oocytes. A number of mammalian species are challenging for embryos/oocytes cryopreservation due to the excessive lipid droplet (LD) content (10-12). The problem of high lipid content in oocytes and embryos seems to concern virtually all the representatives of the Carnivora order (5,12), among which a large proportion are endangered species.…”
Section: Introductionmentioning
confidence: 99%
“…A number of mammalian species are challenging for embryos/oocytes cryopreservation due to the excessive lipid droplet (LD) content (10-12). The problem of high lipid content in oocytes and embryos seems to concern virtually all the representatives of the Carnivora order (5,12), among which a large proportion are endangered species. At least, 28 of 38 extant species of Felidae family are either already considered as endangered/vulnerable or will get this status in the nearest future.…”
Section: Introductionmentioning
confidence: 99%
“…It emerged in the 80s and has since offered a rapid, sensitive approach that is well suited for obtaining chemical profiles from unfractionated complex mixtures of biorelevant molecules (Burlingame, Boyd, & Gaskell, ), proteins and peptide sequencing (González, Iloro, Durán, Elortza, & Suárez, ), and PL research (Schiller et al, ). In the field of animal reproduction, MALDI‐MS has also been extensively used for the investigation of the lipid composition of single embryos, oocytes and blastocysts, human ruminantia and feloideae spermatozoa through the detection of sphingomyelins, phosphatidylcholines, and triacylglycerols; see the works of Schiller et al (), Leßig et al (), Fuchs et al (), Ferreira et al (), Apparicio et al (), Sudano et al (), and Tata et al (). A mass spectrum represents the relative abundances of ions with various m / z values.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are not just "building blocks" in cells; they also play active roles in various cellular functions and can form 9,000 to 100,000 different molecular species (BENNETT;TIELEMAN, 2013). Numerous studies have indicated that the lipid composition of an oocyte or embryo can affect its viability after cryopreservation (APPARICIO et al, 2012;SUDANO et al, 2012). Lipid composition may also be related to embryo viability, and omics-based technologies should contribute significantly with the comprehension of this question (FERREIRA et al, 2010(FERREIRA et al, , 2012a(FERREIRA et al, , b, 2014GONÇALVES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was reported a direct analysis by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) of single and intact embryos or oocytes from different species (APPARICIO et al, 2012;FERREIRA et al, 2010FERREIRA et al, , 2012a. MALDI-MS allows not only a fast and efficient detection of various lipids classes, but also the study of their structure by fragmentation (MS/MS) experiments.…”
Section: Introductionmentioning
confidence: 99%